BRAND LOYALTY IN HIGHER EDUCATION INSTITUTION: THE EFFECTS OF BRAND AWARENESS AND BRAND ASSOCIATION MODERATED BY BRAND IDENTITY - Milcha Handayani Tammubua (Indonesian Journal of Economics, Entrepreneurship, and Innovation, 2021)
This study analyzes the effects of brand awareness and brand association on brand loyalty in the higher education sector and analyzes the role of brand identity as a moderating variable. This research used 182 respondents of Universitas Terbuka (Indonesian Open University) as the sample, which the obtained data through distributing the questionnaires to respondents. Data were analyzed using the SEM-PLS method with the help of SmartPLS software. The results showed that brand awareness and associations had a positive and significant effect on brand loyalty. In addition, this study also confirms the role of brand identity as a moderating influence of brand awareness on brand loyalty. The influence of brand awareness on brand loyalty will be more substantial when higher education has a strong brand identity.